Testing the Four Basic Language Skills in the English Language Component of the Mature Students' Entrance Examinations: The Case of Six Ghanaian Universities - Asafo-Adjei, Ramos (Mediterranean Journal of Social Sciences, 2022)
This study focused on the Mature Students’ Entrance Examinations (MSEE) which is a commonly used Ghanaian university placement examination. The fundamental aim was to evaluate the comprehensiveness of the English language component of the examination in the area of the four basic language skills (Reading, Writing, Speaking and Listening) tested. A second objective of the study was to explore the reasons behind the choices of the basic language skills tested in the MSEE. The multiple case study design was employed for this study, and the sources of data used were responses from in-depth interviews and the past questions. The data were subjected to analysis via thematic content analysis and document analysis respectively. The analysis highlights the specific contents of the past questions and their related basic language skills tested, as well as the reasons underlying the basic language skills tested. The results revealed that only two of the basic language skills (Reading and Writing) were tested, and time limitations and logistical challenges informed lecturers’ decisions not to test Speaking and Listening. The study recommends that Listening and Speaking tasks be incorporated into the examination to make it comprehensive. Received: 2 September 2021 / Accepted: 16 November 2021 / Published: 5 January 2022